The Relationship Between Cognitive Reading and Reading Comprehension Ability of Students at SMAN 1 Kampar Kiri Tengah - Anggi Ariani Br Sitepu; Prih Febtiningsih; Wandi Syahfutra (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on the relationship between cognitive reading and reading comprehension ability of class XI students of SMAN 1 Kampar Kiri Tengah. This research was motivated by the fact that some students still have difficulty in understanding English texts even though they have used certain reading strategies. The method used was quantitative method with correlational approach. The total population in this research was 49 students, with the research sample consisting of 30 students from class XI.6 and 19 students from class XI.5. The instruments used were Cognitive Reading Questionnaire and reading comprehension test. Data analysis was conducted by Pearson Product Moment test using SPSS version 2023. The results showed that there was no correlation between cognitive reading and students' reading comprehension ability. This is indicated by the significance value of 0.710 which is greater than 0.05, so Ha is rejected. Thus, it can be concluded that there is no significant relationship between the two variables. It is expected that teachers and schools can develop more effective reading learning methods to improve students' reading comprehension.